Furvina (G-1) in vitro effectiveness on microorganisms isolated from skin infections in dogs - Díaz Díaz, Miriam (2016)
The aim of this study was to evaluate the in vitro activity of furvina against microorganisms isolated from the skin of canines with piodermatitis in of Santa Clara, Cuba. Resistance to antibacterial agents was assessed by the diffusion method in agar and the in vitro activity was evaluated quantitatively by the broth macrodilution method according to international clinical laboratory standards. Fifty multiresistant strains were identified, 47 from the genus Staphylococcus and 3 from Pseudomonas. The Fisher’s exact test showed highly significant sensibility of microorganisms of the genus Staphylococcus to ciprofloxacin. All strains were resistant to at least three antimicrobials. The Minimum Inhibitory Concentration (MIC) for furvina ranged from 2-16 mg/ml where 83.2% of the strains having a MIC of 4-8 mg/mL. The Minimum Bactericidal Concentration (MBC) ranged from 4-32 mg/ml where 86.2% of the isolates oscillating between 8 and 16 mg/ml. All strains showed a MIC50 against furvina of 5.59 μg/ml (4.70-6.48) and a MBC50 of 11.8 μg/ml (10.0-13.6). These results may infer that furvina exhibits an in vitro bactericidal activity against sensitive and resistant bacteria from canine skin lesions.